2011
DOI: 10.1017/s0007114511002844
|View full text |Cite
|
Sign up to set email alerts
|

Is physical activity in weight management more about ‘calories in’ than ‘calories out’?

Abstract: )In the field of obesity research, physical activity has traditionally been considered a strategy to use energy. Most treadmills and exercise bikes display 'calories' and many people are obsessed about burning those extra 'calories', often only to eat or drink them right back. Although the results of exercise programmes designed to reduce body weight are generally considered disappointing, there is no doubt that some individuals can experience substantial weight loss with regular physical activity. In recent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The resulting weight loss in the present trial comprised exclusively of fat mass, demonstrating that even a modest exercise-induced weight loss can be a meaningful "healthy" weight loss (11,47). Current guidelines for physical activity varies somewhat between countries, but in the adult population, ϳ150 min of physical activity per week (54, 59) or 30 min/day (44) is generally recommended to benefit health, while higher doses of physical activity are often recommended to obtain weight loss or to prevent weight gain (27).…”
Section: Discussionmentioning
confidence: 64%
“…The resulting weight loss in the present trial comprised exclusively of fat mass, demonstrating that even a modest exercise-induced weight loss can be a meaningful "healthy" weight loss (11,47). Current guidelines for physical activity varies somewhat between countries, but in the adult population, ϳ150 min of physical activity per week (54, 59) or 30 min/day (44) is generally recommended to benefit health, while higher doses of physical activity are often recommended to obtain weight loss or to prevent weight gain (27).…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the idea that physical inactivity could compromise appetite regulation was recognized by Henry Taylor in the 1970s, who related the homeostatic control of appetite to the physical activity performed: It has been proposed that the ability to detect over-or-under-consumption is improved at higher levels of habitual physical activity, with a stronger coupling between energy intake and energy expenditure seen in those with higher total daily energy expenditures (120). Indeed, some have suggested that the primary rationale for promoting physical activity may not relate to the increased energy expenditure associated with such activity, but the effect physical activity has on the sensitivity of appetite regulation (121). Cross-sectional studies have shown that habitually active individuals are able to better compensate for high-energy preloads during subsequent feeding episodes than their sedentary counterparts (122,123).…”
Section: Sedentary Behavior As a Pathway To Obesitymentioning
confidence: 99%
“…Hence, it is difficult to agree on which kind of physical activity should be recommended for effective weight control [26]. Whereas some studies and guidelines recommend vigorous physical activity [27,28], other evidence suggests that low-intensity activities such as walking, yoga, meditation and stretching are equally effective in reducing weight [2830]. Second, energy expenditure might be assessed through technological tools aiming to enhance accuracy, such as pedometers and accelerometers, which measure walked distances and estimate the energy expenditure based on the weight, age and height of an individual.…”
Section: Concept 1 To Avoid or Reduce Overweight And Obesitymentioning
confidence: 99%